Institutional health communication and social media: Exploring Italian hospitals’ use of social media pages - Carlotta Fiammenghi; Loredana Covolo; Anna Vanoncini; Umberto Gelatti; Elisabetta Ceretti (Digital Health, 2024)
Introduction Hospitals play a potentially crucial role in public health, and social media can be powerful tools to reach their target audiences but are hospitals exploiting them to their full potential? Methods We retrieved the institutional webpages and the social media profiles (Facebook, Instagram, X (Twitter), YouTube, LinkedIn, WhatsApp and Telegram) of all Italian public hospitals located in regional capitals ( N  = 194). From 1 March to 30 April 2022, we analysed these profiles, noting the number of followers and of posts published, the date of the last post, and the availability of a social media policy. We selected the most active 53 social media profiles (belonging to 33 hospital facilities) for a closer content analysis. Engagement was measured through numbers of reactions, comments and shares to posts published from 1 to 30 April 2022. Results About 36.6% of hospitals had a social media profile, and 18.3% had a social media policy. Most (87%) used Facebook as their main platform. They posted most frequently about hospital events and activities (48.3% of the socially active set). Overall, engagement was modest, as on average 0.62% of potential users reacted to a post. The same post often appeared without modifications across different platforms (82.3% of cases for Instagram, 37.8% for X (Twitter) compared to Facebook). Conclusions Italian public hospitals did not seem to have a clear social media policy nor strategy, and social media remained underused. Italian hospitals, therefore, appeared to be missing valuable opportunities to reach out to their patients and communities.